Sustainable Water Provision Model for Morowali Industrial Area: A System Dynamics Model - Widyadwiana, Amanda; Utami, Citra Fadhilah (Syntax Literate, 2024)
This study aims to investigate the availability of clean water in KI Morowali through a dynamic system analysis, considering the key strategic area's (Morowali Industrial Area, MIA) role in providing water for industrial and residential purposes. By 2026, the traditional water sources are expected to fall short of meeting the increasing demands from both sectors. To address this challenge, the study proposes integrating regional water supply sources, dam utilization, and promoting green open spaces (GOS) within the industrial park area. The method utilized involves analyzing the relationships between various variables impacting water availability. The results highlight the potential for significantly improving MIP's water supply by optimizing catchment zones, increasing GOS in private areas, and adopting a holistic approach to sustainable water management. This comprehensive strategy aims to ensure resilient water resources for Morowali's future needs, mitigating water scarcity challenges effectively.